Design and Construction of a NodeMCU-Based Heart Rate and Blood Oxygen Level Monitoring Device with Blynk Application Output - Miftahurrohman; Asni Tafrikhatin; Jati sumarah; El Vionna Laellyn Nurul Fatich (Politeknik Piksi Ganesha Indonesia, 2025)
Health is a crucial aspect of human life that must be maintained and monitored regularly, especially during recovery periods or self-isolation. Real-time and remote body monitoring has become an essential need in today’s digital era. This study aims to design and develop a heart rate and blood oxygen saturation monitoring device based on the Internet of Things (IoT) using the NodeMCU ESP8266 microcontroller integrated with the MAX30100 sensor and the Blynk application. The research method involves the design of an electronic system based on microcontrollers, software programming, and direct functional testing. The test results show that the device is capable of accurately detecting heart rate (BPM) and oxygen saturation (SpO2), displaying the data on a 16x2 LCD, and transmitting it to the Blynk application in real-time via a WiFi connection. Therefore, the developed device has proven to function effectively as a practical and portable remote health monitoring system.